Effects of dietary l-carnosine supplementation on the growth, intestinal microbiota, and serum metabolome of fattening lambs - Meng, Yaxuan; Xian, Tingting; Kang, Guolei; Wang, Hongna; Feng, Tao (Frontiers in Veterinary Science, 2025)
Dietary l-carnosine supplementation has been shown to enhance animal performance and improve meat quality. However, the mechanisms underlying the effects of l-carnosine on the physiological functions of animals have not been fully elucidated. We investigated the effects of dietary l-carnosine supplementation on growth performance, intestinal microbiota diversity, and the serum metabolome in fattening lambs to reveal the molecular mechanism underlying the effect of l-carnosine on the growth performance of sheep. Sixty 3-month-old male crossbred lambs (Dorper ♂ × Small Tail Han ♀) with an average body weight of 30 ± 5 kg were randomly divided into two groups: a control group (group C) fed a basal diet, and an experimental group (group L) fed a basal diet supplemented with 400 mg/kg of l-carnosine. At the end of the 60-day experiment, all sheep were weighed, and fecal and blood samples were collected from 12 random sheep. The fecal microbiota was analyzed using 16S rRNA sequencing, and serum metabolites were analyzed using liquid chromatography–tandem mass spectrometry. Spearman correlation analysis was employed to assess the associations between intestinal microbiota and serum metabolite biomarkers. The results showed that weight gain and daily weight gain were significantly increased in group L compared to group C (p < 0.01). The dominant phyla in the intestinal microbiota (Firmicutes and Bacteroidetes) did not significantly differ between the two groups (p > 0.05). At the genus level, the abundances of Syntrophococcus (p < 0.01) and Butyricimonas (p < 0.001) were higher, whereas those of Escherichia-Shigella and Candidatus Saccharimonas were significantly lower in group L than in group C (p < 0.05). Non-targeted metabolomics identified 68 differentially abundant biomarkers (VIP > 1, p < 0.05). The content of pyridine N-oxide glucuronide was significantly downregulated (p < 0.01), whereas those of l-histidinol, d-apiose, and isodomedin were significantly upregulated in group L versus group C (p < 0.001). Holdemania and Butyricimonas were positively correlated with l-histidine, d-apiose, and l-erythrulose (p < 0.001), whereas Butyricimonas was negatively correlated with pyridine N-oxide glucuronide (p < 0.001). This study provided new insights into the effects of l-carnosine on the intestinal microbiota and nutrient metabolism in fattening sheep that will be helpful for the future application of l-carnosine in ruminants.